Return to School of Dropout Single Mothers: A School-Family-Community Partnerships Perspective - Deslandes, Rollande; Rivard, Marie-Claude; Duguay, Paula; Lalande, Claire (International Journal about Parents in Education, 2023)
There are few studies on those who resume their education after dropping out of high school and fewer still on single mothers who decide to return to school. The present study, initiated by the organization ‘Mamanva à l’école’ (MVE)(Mom Goes to School), aims to (1) identify the facilitating elements and challenges encountered by single mothers enrolled in general adult education and vocational training and (2) identify ways of supporting them in their roles as students and parents in order to foster their retention and achievement as well as their parental skills for educating their children and getting involved in their schooling. Conducted by means of six group interviews with 39 single mothers and analyzed using a qualitative approach, the study reveals needs specific to the reality of the participants’ lives. For instance, some express the desire to form a separate group apart from young students. They are clear about their need for daycare in their learning centers. These findings can inspire MVE in its mission and guide the Tracking Table in deciding what avenues to privilege in the next stages of a school-family-community partnership regarding mothers’ relations to school and to children’s school learning.